The properties of native and denatured DNA in buoyant rubidium trichloroacetate at neutral pH - Burke, Rae Lyn (1977)
Aqueous RbTCA is generally suitable as a buoyant solvent for both native and denatured DNA at neutral pH and room temperature. Native PM-2 DNA II, for example, is buoyant at 3.29 M salt, 25°C; whereas the denatured strands band together at 4.52 M. Two properties of the solvent make this system uniquely useful for separations based upon the extent of secondary structure. First, the melting transition temperature for chemically unaltered DNA is depressed to room temperature or below. Second, the buoyant density increase accompanying denaturation is extraordinarily large, 174 mg/ml for PM-2 DNA II. This value is three times that found in aqueous NaI and ten times that for CsCl. The properties of the RbTCA buoyant solvent presented here include the compositional and buoyant density gradients and the buoyant density dependence upon base composition. The DNA remains chemically unaltered after exposure to RbTCA as shown by the absence of strand scissions for closed circular DNA and by the unimpaired biological activity in transformation assays. Intact virion DNA may be isolated by direct banding of whole virions in RbTCA gradients without prior phenol extraction. Strongly complexed or covalently bound proteins may be detected by their association with the buoyant polymer in the denaturing density gradient.